Time‐dependent simulation of ion stopping: Charge transfer and electronic excitations. Issue 6 (22nd March 2019) - Schlünzen, N.; Balzer, K.; Bonitz, M.; Deuchler, L.; Pehlke, E.
Abstract : The energy loss of charged particles in matter has been studied for many decades, both, analytically and via computer simulations. While the regime of high projectile energies is well understood, low energy stopping in solids is more challenging due to the importance of non‐adiabatic effects and electronic correlations. Here we consider two problems: the charge transfer between substrate and projectile and the role of electronic correlations, specifically formation of doubly occupied lattice sites in the material during the stopping process. The former problem is treated by time‐dependent density functional theory simulations and the latter by non‐equilibrium Green functions.